HUBUNGAN KEPATUHAN DALAM MINUM OBAT ANTIHIPERTENSI (AMLODIPINE) TERHADAP PENURUNAN HIPERTENSI PADA PASIEN DI PUSKESMAS CIKUYA - Tuti Wahyuningsih; Dewi Puji Astuti; Lastri Mei Winarni (Nusantara Hasana Journal, 2022)
Background high blood pressure in the most common disease in several countries. The american heart association (AHA), people with hypertension without a trigger (Ministry of Health,2014). Healing high blood pressure drugs an modifying their behavior. Methods this type of research uses the chic-square test with probality sampling techinuque for taking 130 samples. Result the result of the chic-square test show that the p-value is 0.588 (0.588 >0.05), which means that there is a not significant relationship between hypertension and hypertensin medication adherence in hypertensive patients. Conclusion there is a relationsship between adherence in taking antihypertensive drugs (amlodipine) to reducing hypertension in patients at the cikuya public health center.